Study on genetics of yield component traits under salt stress in two rice crosses raised using honeycomb selection design - C. Yoglakshmi, Rajan Isha Pearl, V. Vengadessan, J. Karthick and S. Thirumeni* (Electronic Journal of Plant Breeding)
Yield components related to grain yield were severely affected by salinity. For the agronomically important traits, precise phenotyping of crop plants is essential under stress where soil heterogeneity is aggravated for genetic analysis and developing improved crop varieties. A set of two F2 populations obtained from ADT(R)45 × FL478 (A × F) and ADT(R)45 × Nona Bokra (A × N) crosses along with check variety CSR10 were raised in Honeycomb Selection Design (HSD) to study the genetics of yield component traits under salt stress. The study found that the trait, panicle weight in A × F exhibited normal distribution while the other traits exhibited non-normal distribution in both the crosses. Negative skewness was observed for panicle length in both the crosses and days to flowering in the A × N indicating duplicate (additive × additive) gene interactions. Whereas positive skewness was observed for plant height, number of tillers, productive tillers and single plant yield in both the crosses, days to flowering and spikelet sterility in A × F and panicle weight in A × N indicating complementary gene interactions. Leptokurtosis was observed for days to flowering in the A × F. While the remaining characters in both the crosses exhibited platykurtosis. Transgressive segregants in both directions (towards both the parents) were obtained for all the eight characters studied in both the crosses suggesting that all traits were governed by additive gene action. Honeycomb selection design (HSD) provides an excellent phenotyping framework for studying the genetics of any quantitative traits, particularly yield and its component traits, as well as for breeding varieties that will provide more consistent results in yield in a shorter time frame.